2002
DOI: 10.1074/jbc.m202832200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Protein Kinase C Activation and Cell Survival/ Cell Cycle Genes in Green Tea Polyphenol (−)-Epigallocatechin 3-Gallate Neuroprotective Action

Abstract: Studies from our laboratory have demonstrated that the major green tea polyphenol, (؊)-epigallocatechin 3-gallate (EGCG), exerts potent neuroprotective actions in the mice model of Parkinson's disease. These studies were extended to neuronal cell culture employing the parkinsonism-inducing neurotoxin, 6-hydroxydopamine (6-OHDA). Pretreatment with EGCG (0.1-10 M) attenuated human neuroblastoma (NB) SH-SY5Y cell death, induced by a 24-h exposure to 6-OHDA (50 M). Potential cell signaling candidates involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
326
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(348 citation statements)
references
References 57 publications
21
326
1
Order By: Relevance
“…Interestingly, we observed a decrease in the levels of MDM2 protein in response to EGCG treatment. We speculate that this decrease may be directly mediated by EGCG at the transcriptional level (Levites et al, 2002) or as a result of EGCG-mediated increase in p14 ARF levels (Jackson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we observed a decrease in the levels of MDM2 protein in response to EGCG treatment. We speculate that this decrease may be directly mediated by EGCG at the transcriptional level (Levites et al, 2002) or as a result of EGCG-mediated increase in p14 ARF levels (Jackson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that dietary factors can activate apoptosis (Ahmad et al, 1997). Recent studies indicate that green tea and its polyphenolic constituents exert inhibitory effect on the activity of several enzymatic and metabolic pathways of relevance to the development and progression of cancer (Levites et al, 2002;Pianetti et al, 2002). EGCG, by virtue of its ability to selectively induce apoptosis in cancer cells and not in normal cells, is potentially an important cancer chemopreventive agent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these effects, recent studies have also indicated that they are capable of modulating signal transduction pathways and of regulating gene expression, and that these effects may also contribute to the neuroprotective effects of these compounds (29,167) . For example, in vitro and in vivo studies suggest an ability of green tea catechins to regulate apoptotic pathways (168,169) as well as cell survival-related kinase signalling pathways, such as mitogen-activated protein kinase (170) , PKC (171) and phosphoinositide 3-kinase-Akt (172) . A great deal of research has been devoted to the ability of green tea catechins, especially EGC-3-gallate, to activate the PKC pathway (171,173,174) .…”
Section: Green Teamentioning
confidence: 99%
“…For example, in vitro and in vivo studies suggest an ability of green tea catechins to regulate apoptotic pathways (168,169) as well as cell survival-related kinase signalling pathways, such as mitogen-activated protein kinase (170) , PKC (171) and phosphoinositide 3-kinase-Akt (172) . A great deal of research has been devoted to the ability of green tea catechins, especially EGC-3-gallate, to activate the PKC pathway (171,173,174) . Notably, a 2-week pretreatment with a green tea catechin (EGC-3-gallate) was shown to be protective against Ab-induced neurotoxicity by attenuating the depletion of PKC isoforms in the hippocampus and decreasing amyloid precursor protein (173) .…”
Section: Green Teamentioning
confidence: 99%
“…For example, the neuroprotective action of one of the green tea flavonoids, epigallocatechin gallate, has been shown in both oxidative stress-(4) and A␤-induced (5) neuronal death models. Protective effects in both systems were linked to a modulation in signaling through protein kinase C and/or modulation of cell survival/cell cycle genes (4,6). Much evidence also exists to support the potential beneficial and neuromodulatory effects of flavonoid-rich ginkgo biloba extracts, such as EGb 761, in the central nervous system (7)(8)(9).…”
mentioning
confidence: 99%